2007
DOI: 10.1152/ajpregu.00207.2006
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide downregulates the aortic l-arginine/nitric oxide pathway in rats

Abstract: The aim of the present study was to investigate the effect of hydrogen sulfide (H(2)S) signaling by nitric oxide (NO) in isolated rat aortas and cultured human umbilical vein endothelial cells (HUVECs). Both administration of H(2)S and NaHS, as well as endogenous H(2)S, reduced NO formation, endothelial nitric oxide synthase (eNOS) activity, eNOS transcript abundance, and l-arginine (l-Arg) transport (all P < 0.01). The kinetics analysis of eNOS activity and l-Arg transport showed that H(2)S reduced V(max) val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 54 publications
0
84
0
Order By: Relevance
“…25 However, higher doses caused a biphasic relaxation/constriction response, the mechanism of which warrants further study. H 2 S can contract isolated blood vessels either by quenching released NO, 13 by inhibiting endothelial NO synthase, 26 or by oxidation of H 2 S to a vasoconstrictor molecule in conditions of high oxygen tension. 27 Bolus injection of GYY4137 did not affect renal perfusion pressure, presumably because the drug is washed out of the tissue before sufficient breakdown to H 2 S occurs.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, higher doses caused a biphasic relaxation/constriction response, the mechanism of which warrants further study. H 2 S can contract isolated blood vessels either by quenching released NO, 13 by inhibiting endothelial NO synthase, 26 or by oxidation of H 2 S to a vasoconstrictor molecule in conditions of high oxygen tension. 27 Bolus injection of GYY4137 did not affect renal perfusion pressure, presumably because the drug is washed out of the tissue before sufficient breakdown to H 2 S occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the production of H 2 S can be upregulated by NO (49,57). Most recently, Geng et al (17) have shown that eNOS (vs. inducible NOS and neuronal NOS) may be the specific target of H 2 S regulation in rat aortas (50). Thus we evaluated the role of eNOS in the vasculoprotection afforded by late-phase H 2 S-PC by employing a pharmacological inhibitor approach in WT animals and using an eNOS knockout model.…”
Section: Discussionmentioning
confidence: 99%
“…24) Two main intracellular action sites of H 2 S are known from different cell systems. This includes the ability of H 2 S to stimulate ATPsensitive K ϩ channels, an effect that is well characterized e.g.…”
Section: Hydrogen Sulfidementioning
confidence: 99%